A Model of Granular Materials Cemented by Bacterial Calcite - Kashi, Ella (Curtin University, 2019)
Nature aggregates granular materials such as sand, silt and clay into form beach rocks, and other forms of microbialites. A common bio-geo-chemical cementation occurs due to the mineralization of calcium through bacterial enzymatic action, often called Microbial Induced Calcium Carbonate Precipitation (MICP). It is a sustainable construction method. Experimental and Numerical models are presented to study the aggregated granular materials formed due to MICP. The models are applied to investigate different levels of aggregation of sand. The numerical results are compared against experiments and the most important parameters are discussed.